Chronic diseases and association with abnormal body mass index (BMI)among adults in Kg. Bukit sekilau, Kuantan - Mohd Rus, Razman; Ab Rahman, Jamalludin (2011)
A cross – sectional study was conducted in Kampung Bukit Sekilau, Kuantan, Pahang with the aim to measure the prevalence of chronic diseases (Hypertension, Diabetes Mellitus and Coronary Artery disease) among adults population age 18 and above and factors associated (abnormal body mass index (BMI), age, gender and family history). Simple random sampling was used. Face to face interviews were conducted by trained survey teams using standardized questionnaire. Known diabetes and coronary artery disease were by self-reported. Blood pressure was determined using questionnaire and blood pressure measurements. A total of 360 respondents participated in this study. 99.2% of the respondents were Malay with mean age of 43.4 (SD =16.1) years old. More than half (59.2%) of the respondents were female. 99.2% had formal education and 71.4% were married. The prevalence of diabetes and coronary artery disease were found to be 11.9% and 3.1% respectively. The overall prevalence of hypertension (known and newly diagnosed) was 36.1%. In addition, 37.5% of the respondents were found to be obese and 31.7% were overweight. Logistic regression analysis revealed that abnormal BMI is significantly associated with hypertension (p = 0.003). However, abnormal BMI was found not significantly associated with diabetes (p = 0.381) and coronary heart disease (p = 0.239). In conclusion, the prevalence of chronic diseases together with prevalence of overweight and obesity has risen in the last decade. Therefore, an effective public health program to control the situation is very much needed.